A pilot clinical trial of intravesical mitomycin-C and external deep pelvic hyperthermia for non-muscle-invasive bladder cancer. (May 2014) - Inman, Brant A.; Stauffer, Paul R.; Craciunescu, Oana A.; Maccarini, Paolo F.; Dewhirst, Mark W.; Vujaskovic, Zeljko
Abstract Purpose: This paper aims to evaluate the safety and heating efficiency of external deep pelvic hyperthermia combined with intravesical mitomycin C (MMC) as a novel therapy for non-muscle-invasive bladder cancer (NMIBC). Materials and methods: We enrolled subjects with bacillus Calmette-Guérin (BCG) refractory NMIBC to an early phase clinical trial of external deep pelvic hyperthermia (using a BSD-2000 device) combined with MMC. Bladders were heated to 42 °C for 1 h during intravesical MMC treatment. Treatments were given weekly for 6 weeks, then monthly for 4 months. Heating parameters, treatment toxicity, and clinical outcomes were systematically measured. Results: Fifteen patients were enrolled on the clinical trial. Median age was 66 years and 87% were male. Median European Organisation for Research and Treatment of Cancer (EORTC) recurrence and progression scores were 6 and 8, respectively. The full treatment course was attained in 73% of subjects. Effective bladder heating was possible in all but one patient who could not tolerate the supine position due to lung disease. Adverse events were all minor (grade 2 or less) and no systemic toxicity was observed. The most common adverse effects were Foley catheter pain (40%), abdominal discomfort (33%), chemical cystitis symptoms (27%), and abdominal skin swelling (27%). With a median follow-up of 3.18 years, 67% experienced another bladder cancer recurrence (none were muscle invasive) and 13% experienced an upper tract recurrence. Conclusions: External deep pelvic hyperthermia using the BSD-2000 device is a safe and reproducible method of heating the bladder in patients undergoing intravesical MMC. The efficacy of this treatment modality should be explored further in clinical trials.